Addition of estradiol cypionate and (or) calf removal to a modified MGA + CO-Synch protocol for fixed-time artifical insemination of beef cows - Johnson, Sandra K.; Harmoney, Keith R.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study was conducted in 735 suckled beef cows to determine if synchronization of ovulation could be improved with estradiol cypionate (ECP) and(or) 48-hour calf removal in a modified MGA + CO-Synch protocol. All cows were fed melengestrol acetate (MGA) (0.5 mg/cow) daily for 14 days (days -32 to - 19 of the experiment) and received an injection of gonadotropin-releasing hormone (GnRH) on d -7, an injection of prostaglandin F2α (PGF) on day 0, and received a fixed–time artificial insemination (AI) at 72 hours after PGF. Treatments were applied in a 2 x 2 factorial arrangement. Calves either remained with cows (suckled) or were removed for 48 hours, beginning 24 hours after PGF and continuing until after the fixed-time AI (calf removal). Cows received either ECP at 24 hours after PGF or received GnRH concurrent with the fixed-time AI. AI pregnancy rates were similar for cows receiving ECP (48%) or GnRH (45%). Cycling status influenced the response to calf removal. Noncycling cows whose calves were removed had greater AI pregnancy rates than suckled cows, 37% vs. 27%, respectively. When calves were not removed, GnRH given at fixed-timed AI resulted in pregnancy rates similar to ECP and did not require additional handling of the cows. In the herd of mature cows with body condition scores near 5 and that had calved 75 to 80 days before the time of AI, the MGA + CO-Synch system used in this study produced AI pregnancy rates of 50% or better without heat detection.
Keywords: Beef; Estradiol cypionate; Calf removal; MGA + CO-Synch; Gonadotropin-releasing hormone